1388 Diabetes, cardiovascular disease, psychosocial distress and other risks among australian farmers and agricultural communities – health surveillance and outcomes. (24th April 2018) - Brumby, Susan; Rahman, Muhammad Aziz; Lewis, Joe; Hatherell, Tracey; Phillips, Tam
Abstract : Background: Farmers and rural populations have increased risk of cardiovascular disease, diabetes and suicide compared to general Australians. They also encounter problems of equitable access of expertise, exacerbated by large distances. If risk factors are identified or prevented then better health outcomes should follow for this high risk group. There is also a lack of cultural competence in health professionals around agricultural work, and its occupational and lifestyle risks. Methods: A cross-sectional study was conducted across rural Australia on 1697 participants during 2009–2016 at agricultural events to explore the behavioural, cardiovascular and diabetes risks among the farming community. Study participants were >18 years of age, spoke English and were involved/associated with farming. Diabetes risk was assessed by the validated AUSDRISK tool and cardiovascular risk through a 20 min one- on- one assessment—anthropometric measures, blood cholesterol, blood glucose, blood pressure, psychosocial distress, and waist measurement. Participants were provided with health information relevant to their risks and also recommended for further follow up. Results: Mean age was 53 (±15.5) years, 62% was male and 58% were farmers/agricultural workers. More than two-thirds (73%) were overweight/obese; no difference between farmers and non-farmers. Males were more likely to undertake short term risky alcohol use compared to females (62% vs 46%), although both were higher than Australian rates. 55% were at risk of developing type 2 diabetes within 5 years; males (90% vs 79%, RR1.14, 95% CI: 1.09 to 1.20) and farmers (88% vs 83%) were at increased risk. Hypertension (≥140/90 mmHg) was 44% and more common in males and farmers. In 2016, a random selection (150) were contacted to evaluate change in their behaviours and engagement with health practitioners since the intervention with surprising outcomes. Conclusion: Health surveillance and occupationally sensitive placed-based interventions for farming/rural populations should be the primary focus for health promotion strategies.